To Compare the Blood Loss in Bipolar Diathermy Versus Suture Ligation for Hemostasis in Patients Presented with Chronic Tonsillitis - Anees Ur Rehman, Salman Ahmed Mangrio, Muhammad Farooq Bhutta, Ikram Ullah, Ashfaq Hussain Rana, Muhammad Tahir, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the blood loss in bipolar diathermy versus suture ligation for hemostasis in patients presented with chronic tonsillitis Material and methods: We conducted this randomized controlled at ENT Department Sheikh Zayed Hospital Rahim Yar Khan from April, 2022 to September, 2022. Total 70 patients presenting with chronic tonsillitis divided in two groups equally. Patients were treated with two procedures bipolar diathermy and ligation. Mean blood loss and operative time was compared between both groups. T-Test was used for comparison keeping P < 0.05 as statistically significant. Results: Mean age of the patient was 22.86±9.31 years in group A and 22.89±7.29 years in group B. The mean blood loss in group A and group B was 27.71±7.10 ml vs 43.40±16.63 ml. Procedure time in group A and group B was 7.69±1.85 mins vs 9.91±2.09 mins. Conclusion: We conclude that bipolar diathermy group had statistically lower amount of blood loss and post-operative time when compared with ligation group. Keywords: bipolar diathermy, ligation, chronic tonsillitis, hemostasis